Decoding the context of servitization: socio-technical pivots on the journey to service-oriented business models in manufacturing firms - Kurtz, Julian; Meyer, Patrick; Roth, Angela (Production Planning & Control, 2023)
Servitization has been discussed in academia and practice for decades, but there is still a lack of concrete guidance for manufacturing firms to orchestrate their servitization journeys. This study addresses this deficiency by analysing 88 annual reports of manufacturing firms. Using a multi-cycle inductive coding approach, six pivotal factors in servitization journeys were derived in order to decode their context. The pivotal factors represent fields of action in which manufacturing firms are currently active on their servitization journeys. They include both frontstage (e.g. market proposition) and backstage (e.g. process excellence) factors and predominantly emphasise technological over social activities. This exploratory study contributes to a more nuanced and contextualised understanding of the transformation of manufacturers into service-oriented firms. More importantly, this study sheds new light on servitization research by applying a socio-technical perspective and proposes a practical structuring of the servitization journey with tandems to navigate the journey.<br
Keywords: Servitization; business model innovation; product-service systems; socio-technical system perspective